A vida em três estados : sólido, líquido e gasoso - Machado, Rodrigo Celente (2016)
This paper, placed in the Creative Writing area, has two parts as two mirrors facing each other. They look like the same, but they are different. The collection of narratives (short stories) presents in Life in three states: solid, liquid and gaseous is the result of a process that fictionalized ―liquid modernity‖, the idea introduced by polish sociologist Zigmunt Bauman, with all its variants. The characters are shown desperate, abandoned to their own senses and disposable feelings, yearning for security and personal relations. Everything that is revealed is lie, but also could be true. Or would it be opposite? The reader is left to decide. All that involved before, during and after the intellectual-creative effort is in the essay Giving node in drop of water.